Safety, immunogenicity, efficacy, and effectiveness of Lassa fever vaccines in pregnant persons, children, and adolescents: a protocol for a living systematic review and meta-analysis - Jamile Ballivian; Mabel Berrueta; Agustín Ciapponi; Juan Manuel Sambade; Katharina Stegelmann; Agustina Mazzoni; Ariel Bardach; Martin Brizuela; Daniel Comandé; Noelia Castellana; Edward P. K. Parker; Andy Stergachis; et al. (Reproductive Health)
Abstract Background Lassa fever (LF), caused by the Lassa virus (LASV), is a zoonotic viral hemorrhagic disease endemic to West Africa, primarily transmitted through rodent excreta and infected bodily fluids. It poses significant public health challenges due to its high morbidity and mortality rates, particularly among at-risk populations like pregnant persons and children. Despite decades of research, vaccine development has been hindered by the virus’s genetic diversity and complex epidemiology. While several vaccine candidates have been developed, none have received regulatory approval. Given the rapidly evolving vaccine landscape, a living systematic review (LSR) was selected to enable real-time evidence synthesis. This protocol outlines a living systematic review (LSR) to evaluate the safety, efficacy, effectiveness, and immunogenicity of LASV vaccines, providing evidence to guide public health interventions and vaccine recommendations. Methods We will conduct a biweekly updated LSR and meta-analysis, systematically searching databases (e.g., MEDLINE, EMBASE, CENTRAL) and clinical trial registries from January 2014 onward to identify studies of LASV vaccines in pregnant persons, children, and adolescents. All study designs, including randomized trials, cohort studies, case–control studies, and case reports, will be eligible. Pairs of reviewers will independently assess eligibility, extract data, and evaluate the risk of bias. Primary outcomes include vaccine safety, efficacy, and effectiveness in pregnant persons (including neonatal outcomes), children, and adolescents, while secondary outcomes assess immunogenicity and reactogenicity. Data on adult populations will also be included, and results on this group will be reported as available. We will conduct paired meta-analyses, including prespecified subgroup and sensitivity analyses. We will use the grading of recommendations assessment, development, and evaluation approach to evaluate the certainty of evidence. Discussion This LSR offers a dynamic framework to generate timely evidence on LASV vaccines for vulnerable populations. By integrating findings into an interactive Microsoft Power BI dashboard, stakeholders can access and utilize real-time updates to inform public health strategies. Despite challenges like study heterogeneity and vaccine platform variability, subgroup and sensitivity analyses will mitigate these issues. This review aims to support clinical trial designs, guide policy, and improve health outcomes in Lassa fever-endemic regions. Study registration Two protocols were registered in the International Prospective Register of Systematic Reviews (PROSPERO) database: CRD42024514513 and CRD42024516754.